Design and Construction Optical Fiber Sensor System for Detection the Stress and Fine Motion - Bushra R. Mhdi; Nahla A.Aljabar; Suad M.Ali; Abeer H.Khalid (International Journal of Advances in Applied Sciences, 2013)
Two main concepts in design and construction of stress and fine motion detection system using fiber optic sensor was included in this project. The first is design and construction concept using Intensity Modulation techniques using plastic multimode optical fiber(125μm dim)and has NA(0.27) with losses rate (2.1 db)and directionality about(25 db),and we used (He-Ne)laser source(632.8 nm)with (LLM-2 light power meter) to detect the variation in output laser power due to micro-displacement for movement body under test. The second concept include Modeling for laser beam tracking through fiber and that which reflected for mirror to detector. Variation in output power due to target movement was theoretical analyzed from study of variation of Gaussian front wave profile of using (MATLAB) program within displacement range from(0-5 mm).Non-linear relation between separated distance and beam intensity was investigated. Finally our design are evaluated in comporizim with published research which found compatible in Theoretical and experimental results.